Altmetrics as a means of assessing scholarly output. Issue 5 (1st September 2014) - KHODIYAR, Varsha K.; ROWLETT, Karen A.; LAWRENCE, Rebecca N.
ABSTRACT: Career progression for scientists involves an assessment of their contribution to their field and a prediction of their future potential. Traditional measures, such as the impact factor of the journal that a researcher publishes in, may not be an appropriate or accurate means of assessing the overall output of an individual. The development of altmetrics offers the potential for fuller assessments of a researcher's output based on both their traditional and non‐traditional scholarly outputs. New tools should make it easier to include non‐traditional outputs such as data, software and contributions to peer review in the evaluation of early‐ and mid‐career researchers.